2013
DOI: 10.1155/2013/715829
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Capacitive Radiofrequency on the Fibrosis of Patients with Cellulite

Abstract: Background. Cellulite is a type of lipodystrophy that develops primarily from an alteration in blood circulation or of the lymphatic system that causes structural changes in subcutaneous adipose tissue, collagen, and adjacent proteoglycans. The radiofrequency devices used for cutaneous applications have shown different physiological treatment effects, but there is controversy about the suitable parameters for this type of treatment. Objectives. The aim of this study was to evaluate the effects of low-temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In recent years, obesity studies have reported that a decrease in oxygen saturation at the tissue level, termed hypoxia , is one of the factors in tissue fibrosis, 4 and hypoxia has attracted attention as a factor that promotes fibrosis. It is considered that the enlargement of fat cells leads to blood vessel compression, which in turn leads to the deterioration of oxygen supply to the tissues, resulting in tissue fibrosis and cellulite 5 . Therefore, it is also important to understand the relationship between oxygen saturation and body conditions such as obesity and musculature.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, obesity studies have reported that a decrease in oxygen saturation at the tissue level, termed hypoxia , is one of the factors in tissue fibrosis, 4 and hypoxia has attracted attention as a factor that promotes fibrosis. It is considered that the enlargement of fat cells leads to blood vessel compression, which in turn leads to the deterioration of oxygen supply to the tissues, resulting in tissue fibrosis and cellulite 5 . Therefore, it is also important to understand the relationship between oxygen saturation and body conditions such as obesity and musculature.…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency energy can be applied to body skin to create tightening without surgical incisions and recovery time . Immediate abdominal skin tightening and fat reduction were clinically observed in several studies, with a high satisfaction rate. The benefit of RF in terms of reduction of abdomen and cellulite appearance is today well established .…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning and end of the study, an ultrasound examination was performed in the gluteal region, delimited by a mold in a 10 cm 2 area, which allowed to evaluate the transformation of the fibrous septa and fat layer in the area with cellulite before and after the proposed treatment. Ultrasonography is considered an efficient diagnostic method to assess fibrous septa integrity and to identify treatment effects on cellulite and on localized fat [18].…”
Section: Methodsmentioning
confidence: 99%